Yield ratios and directed flows of light fragments from reactions induced by neutron-rich nuclei at intermediate energy *Supported by National Natural Science Foundation of China (11405025). (April 2017) - Yan 颜, Ting-Zhi 廷志; Li 李, Long-Long 龙龙; Wang 王, Rui-Feng 瑞丰; Yan 颜, Ting-Feng 廷锋
Abstract: The yield ratios of neutron/proton and 3 H/ 3 He and the directed flow per nucleon for these projectile-like fragments at large impact parameters are studied for 50 Ca + 40 Ca and 50 Cr + 40 Ca for comparison at 50 MeV/u using the isospin-dependent quantum molecular dynamics (IQMD) model. It is found that the yield ratios and the directed flows per nucleon are different for reactions induced by the neutron-rich nucleus 50 Ca and the stable isobaric nucleus 50 Cr, and depend on the hardness of the EOS. The ratios of neutron/proton and 3 H/ 3 He and the difference of directed flow per nucleon of neutron-proton are suggested to be possible observables to investigate the isospin effects.